2009
DOI: 10.1007/s00251-009-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

European wild boars and domestic pigs display different polymorphic patterns in the Toll-like receptor (TLR) 1, TLR2, and TLR6 genes

Abstract: During the last decade, the Toll-like receptors (TLRs) have been extensively studied, and their immense importance in innate immunity is now being unveiled. Here, we report pronounced differences--probably reflecting the domestication process and differences in selective pressure--between wild boars and domestic pigs regarding single nucleotide polymorphisms (SNPs) in TLR genes. The open reading frames of TLR1, TLR2, and TLR6 were sequenced in 25 wild boars, representing three populations, and in 15 unrelated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…In the latter study, six polymorphic microsatellite markers within the genetic regions of TLR1, 6 and 10 were developed as they might be useful in association studies of TLR variants and resistance to disease. According to a more recent study, in the genes coding for porcine TLR1, 2 and 6, a total of 20, 26 and 27 NSSNP were found, respectively (Bergman et al 2010).…”
Section: Pigmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter study, six polymorphic microsatellite markers within the genetic regions of TLR1, 6 and 10 were developed as they might be useful in association studies of TLR variants and resistance to disease. According to a more recent study, in the genes coding for porcine TLR1, 2 and 6, a total of 20, 26 and 27 NSSNP were found, respectively (Bergman et al 2010).…”
Section: Pigmentioning
confidence: 99%
“…Genes expressing all TLR members known in humans and porcine MyD88 have been cloned (Bergman et al 2010;Astakhova et al 2009;Shinkai et al 2006a;Bailey 2009;Tohno et al 2007;Turin and Riva 2008) showing a nucleotide homology of DNA of 65-77% with human TLR orthologues. The gene coding for porcine MyD88 is 87% homologous to the human MyD88 gene.…”
Section: Pigmentioning
confidence: 99%
“…However, the general picture is the opposite, that is, Asian wild boars possess a higher degree of genetic variation than European wild boars (Groenen et al, 2012). Previously, we have shown that European wild boars and domestic pigs display different polymorphic patterns in the TLR1, TLR2, TLR6 (Bergman et al, 2010) and TLR10 (Bergman et al, 2011) genes, indicating the need of different genotypes in different microbial environments and confirming results from cattle (Jann et al, 2008) and mice (Stephan et al, 2007). It is thus tempting to speculate that the mutant alleles of SNPs A77G and T871C, both located in pMBL1 and part of combined pMBL haplotype H8, represent a selective advantage in relation to the microbial environment of Japan and that this microflora is generally less favourable to variation in the MBL genes of wild boars than its counterparts in Sweden, Austria and the Czech Republic.…”
Section: Discussionmentioning
confidence: 91%
“…Its evolutionary history has been shown to be complex and include a deep phylogenetic split between European and Asian animals about 1 million years ago, population bottle necks on both continents, selective sweeps and exchange of genetic material between wild boars and domestic pigs (Groenen et al, 2012). This, in combination with contemporary differences in selection pressure and the unrestrained migration of wild animals, could explain certain discrepancies in findings regarding immunerelated genes in wild boars and domestic pigs (Bergman et al, 2010;Chen et al, 2013). The wild boars included in the present study represent four populations from Europe and Asia.…”
Section: Discussionmentioning
confidence: 93%
“…Currently, about 2,000 heads of Jeju horses are being raised at local ranches. Domestic animals are well suited for genetic studies, since they enable comparisons of populations exposed to different selection criteria and environmental challenges [1, 2]. Jeju horses are very valuable animals to preserve historically and economically and it is very important to investigate unique genetic characteristics of Jeju horses [3, 4].…”
Section: Introductionmentioning
confidence: 99%